2016
DOI: 10.1016/j.ijbiomac.2016.04.039
|View full text |Cite
|
Sign up to set email alerts
|

Pure keratin membrane and fibers from chicken feather

Abstract: In this research, keratin was extracted from the disposable chicken feather using l-cysteine as reducing agent. Then, it was re-dissolved in the sodium carbonate-sodium bicarbonate buffer, and the pure keratin membrane and fiber were fabricated by doctor-blade casting process and wet spinning method, respectively. Scanning electron microscopy (SEM), fourier transform infrared (FT-IR) spectroscopy, X-ray diffraction (XRD) and thermogravimetric analysis (TGA) were used to characterize the chemical and physical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(77 citation statements)
references
References 47 publications
5
57
0
Order By: Relevance
“…2). After comparison of five samples, it was found that the characteristic peaks are similar with each other and are comparable with other studies [26]. On the other hand, the surfactants have little effect on the chemical structure of protein and all the treatments showed transmission bands to the peptide bonds (-CONH) and are known as Amide A, Amide I, Amide II, Amide III [10,27,28].…”
Section: Fourier Transform Infrared Spectroscopy (Ft-ir)supporting
confidence: 85%
“…2). After comparison of five samples, it was found that the characteristic peaks are similar with each other and are comparable with other studies [26]. On the other hand, the surfactants have little effect on the chemical structure of protein and all the treatments showed transmission bands to the peptide bonds (-CONH) and are known as Amide A, Amide I, Amide II, Amide III [10,27,28].…”
Section: Fourier Transform Infrared Spectroscopy (Ft-ir)supporting
confidence: 85%
“…However, keratin particles prepared in our research was irregular in shape, and this is mainly ascribed to the processing method. In our previous research, the pristine precipitated keratin presented spheres with nanoscale, if the pristine precipitated keratin was re‐dispersed in proper solvent and dried by spraying method, the obtained keratin particles were supposed to possess nanospheres, like the results of Zhang et al . 's publication.…”
Section: Resultsmentioning
confidence: 71%
“…This is mainly due to the fact that pure keratin is fragile and has poor mechanical property . In our previous study, the tensile strength of the pure keratin membrane and fibers was only 3.5 MPa and 0.5 cN dtex −1 respectively, although the incorporation of the plasticizer makes the keratin material flexible, the exudation of the plasticizer is another difficult problem to be solved. Therefore, it was more beneficial to develop a keratin‐based composite material.…”
Section: Introductionmentioning
confidence: 93%
“…35 The peak at 1219 cm -1 is characteristic of the stretching vibrations of C-N (amide III). 36,37 By comparison of the spectra of pure keratin and konjac glucomannan films with those of the blended films, it can be seen that, with an increasing amount of glucomannan, the absorption bands at app. 3280 cm -1 and at 2924 cm -1 broadened and shifted to higher wave numbers, which confirmed the introduction of the -OH groups of glucomannan.…”
Section: Resultsmentioning
confidence: 99%